Self-regulated strategy development in ESL writing for academic purposes / Grace Regina Devi a/p J.W. Michael - Grace Regina Devi, J.W. Michael (2013)
Where writing in a second language (L2) is concerned, the task becomes even more complex and demanding because second language writers are often hindered by complications that arise due to proficiency in the target language (TL), knowledge of the target language genres and the sociocultural expectations that are associated with them. However, there is evidence to indicate that an interactive, and scaffolded development of strategies for writing and self-regulation of the writing process through explicit strategy instruction such as Self- Regulated Strategy Development (SRSD) instruction, can positively affect student performance across writing genres. The present study contributes to an existing body of research on SRSD and self-regulation in writing by adding to the few studies that have been done on ESL learners belonging to a particular ethnic or language group. The subjects of this study are low-proficiency Malay learners of English as a Second Language at a public university pursuing an English for Academic Purposes course. This study examines how instruction modelled after the SRSD framework affects the writing skills, self-efficacy and learning strategies of this group of students. Among others, the findings of the paired-sample t-test revealed that the SRSD based writing instruction had a significant positive effect on all four components of the writing skills of the low-proficiency Malay ESL learners as well as their overall use of the language learning strategies. The most frequent use of learning strategies in this ESL academic writing class was the affective strategies, and this was followed by the cognitive strategies and then the metacognitive strategies. The SRSD model also appears to positively affect the self-efficacy of the learners in the treatment. However, iv what was unexpected is that the control group likewise indicated a significant change in the overall perceived self-regulatory efficacy for writing. In terms of the 10 categories of self-regulated learning, significant changes were found in organising and transforming strategies, reviewing records, keeping records and monitoring and lastly, seeking social assistance. The findings serve to increase understanding of the impact such a strategy training programme has on both writing and self-regulated learning strategies, as well as the language learning strategies of low-proficiency Malay learners of English as Second Language. Furthermore, this strategy study also extends another area of research that is teaching EAP through SRSD intervention which up to now has not been adequately explored, especially in the ESL context. Additionally, by investigating the impact of the model on students’ writing self-efficacy, this study also broadens our understanding of the effects of SRSD intervention on students’ self-efficacy for academic writing.